Peran Guru Pendamping Khusus pada Program Layanan Pendidikan Inklusi di TK Idaman Banjarbaru - Siti Liani; Barsihanor Barsihanor; Abdul Hafiz (Universitas Ngudi Waluyo, 2021)
The concept of learning in inclusion education requires the right strategy. The strategy is tailored to the needs of children with special needs. Ability in classroom management is emphasized for a teacher in an inclusion school, in addition, teachers are required to have competencies in managing learning and understanding aspects of children's development. This research aims to find out the role of special companion teachers in the program inclusion education services at Tk Idaman Banjarbaru. The role of a special companion teachers in the inclusion education service program at Tk Idaman Banjarbaru is carried out in several ways, namely: assessing students at the beginning of the new school year by involving psychologists to find out the types and levels of problems that children experience, makingÂ Individual Learning Programs that are suitable for children with special needs, which are carried out through learning in the classroom and also through resource space provided in order to provide stimulus to ABK, and play a role in assessing, and edification of standards / indicators that have been adjusted to the circumstances of students with special needs.